HUBUNGAN HIPERTENSI DALAM KEHAMILAN DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI RS GRAHA JUANDA TAHUN 2018 - Manullang, Riyen Sari (Jurnal Ayurveda Medistra, 2020)
Background: maternal deaths in Indonesia still consider three main causes of death, namely bleeding, hypertension in pregnancy, and infection. However, the proportions have changed, where increased bleeding and infections ultimately lead to hypertension in pregnancy which is increasingly the main cause. More than 25 % of maternal deaths in Indonesia in 2013 were caused by hypertension in pregnancy..Research purposes: to determine the relationship of hypertension in pregnancy with the incidence of low birth weight in Graha Juanda Hospital year 2018.Research method: : Design research analytic with retrospective study design. Population in this study study is the medical record of women with maternal hypertension of pregnancy at the Hospital Graha Juanda in 2018, amounting to 850 people. The sample n this study was a total sampling type, namely by taking all the population of maternity women who experience hypertension in pregnancy. The statistical analysis used is Chi-Squre.Research result: Analysis Chi- Squere shows value test statistics with use t test at get it results pvalue 0.001 then there is a significant hypertension in pregnancy with incidence of low birth weight babies. Conclusion : From the results analysis there is relationship of hypertension in pregnancy with the incidence of low birth weight in Graha Juanda Hospital in 2018